2019
DOI: 10.7238/d.v0i23.3144
|View full text |Cite
|
Sign up to set email alerts
|

The tech entrepreneur in Colombia: a discussion of actor-network-theory, Lacanian theory and social imaginaries

Abstract: The figure of the tech entrepreneur has gained special relevance in the contemporary world. Recognized stories of success such as those of Steve Jobs, Bill Gates and Mark Zuckerberg have popularized worldwide the imagination of the young student who starts a garage company with nothing more than his own passion, intelligence and determination, and becomes a global celebrity and a billionaire in just a few years. Nevertheless, the discourses and cultural productions that shape this figure do not always adhere t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…These interviews were conducted in Spanish by Sebastian Santisteban and were subsequently transcribed and coded for thematic analysis. This sequence of research follows from previous research that included interviews of 144 entrepreneurs in Bogotá (Santisteban, 2018a, 2018b, 2019). As with that earlier research, the study reported here was informed by Lacanian theory and therefore paid particular attention to the dynamics of the signifier.…”
Section: Magic and Entrepreneurship In The Mountains Of Antioquiamentioning
confidence: 99%
See 1 more Smart Citation
“…These interviews were conducted in Spanish by Sebastian Santisteban and were subsequently transcribed and coded for thematic analysis. This sequence of research follows from previous research that included interviews of 144 entrepreneurs in Bogotá (Santisteban, 2018a, 2018b, 2019). As with that earlier research, the study reported here was informed by Lacanian theory and therefore paid particular attention to the dynamics of the signifier.…”
Section: Magic and Entrepreneurship In The Mountains Of Antioquiamentioning
confidence: 99%
“…The reading of entrepreneurship proposed here is only possible because of our individual and shared readings of the works of Jacques Lacan, who has been crucial for us in fundamentally rethinking the place and function of entrepreneurship discourse. Concepts originally developed by Lacan have been applied with considerable success in the understanding of entrepreneurship (Dashtipour and Rumens, 2018; Driver, 2017; Jones and Spicer, 2005; Kenny et al, 2020; Santisteban, 2019) and in a surprisingly wide range of areas in management and organisation studies more generally (for commentary and critique see Arnaud, 2012; Arnaud and Vanheule, 2013; Arnaud and Vidaillet, 2018; Cederström, 2009; Cederström and Hoedemaekers, 2010; Contu, 2020; Contu et al, 2010; Kenny, 2020; Pedersen and Kristensen, 2019). We seek to establish here that critical studies of entrepreneurship in general and Lacanian studies of entrepreneurship in particular will benefit from much further and deeper engagement with the realities of capitalism.…”
mentioning
confidence: 99%